Effects of endophytes on early growth and ascorbate metabolism in Brassica napus - Jones-Held, Susan; White, James F. (Frontiers in Plant Science, 2024)
Understanding the early interactions between plants and endophytes will contribute to a more systematic approach to enhancing endophyte-mediated effects on plant growth and environmental stress resistance. This study examined very early growth and ascorbate metabolism after seed treatment of Brassica napus with three different endophytes. The three endophytes used were Bacillus amyloliquefaciens pb1(Bapb1), Micrococcus luteus (Ml) and Pseudomonas fluorescens SLB4 (SLB4). Seeds of Brassica napus cv. trophy were surface sterilized and plated on 1/2 MS Basal salts (pH 5.7 -5.8) + 0.8% agarose. Under sterile conditions, endophyte suspensions or sterile distilled water (controls) were applied to plated seeds. After two days, all plates were scanned to produce digital images for subsequent growth analysis. Then, seedlings were gently removed from the plates and placed in sterile microfuge tubes. For biochemical analyses, extracts were prepared from samples and assayed spectrophotometrically.We detected slight changes in seedling root tip and/or primary root growth with Bapb1 and Ml. Seedlings treated with SLB4 exhibited significantly increased primary root and root tip length after two days of growth. Ascorbate oxidation, however, was the primary significant change common to all endophyte-treated seedlings. In relation to ascorbate oxidation, soluble ascorbate oxidase (AO) was slightly reduced in Bapb1 and Ml-treated seedlings, whereas ionically-bound AO was reduced in Bapb1 and SLB4-treated seedlings. Total AO activity was significantly reduced in Bapb1-treated seedlings. There were no differences in cytosolic APX activity or glutathione levels between endophyte-treated seedlings and controls. Like pathogens, endophytes can trigger an oxidative burst in the plant. A level of ascorbate oxidation seems required to propagate ROS as signaling molecules as part of the plant immune response. The slight to moderate reductions in plant AO activity that we found mimic the inhibitory effects of pathogens on AO activity, but there was still a level of AO activity that may have been sufficient for the apoplastic ascorbate oxidation required for subsequent ROS signaling. Other studies have suggested that endophytes may elicit a more moderate plant immune response relative to pathogens to facilitate colonization. The AO, APX, and glutathione results would be consistent with a moderate plant immune response to endophytes.